(untitled) (Journal of Pharmaceutical Negative Results, 2022)
The data on a comparative study of the antimicrobial activity of lactic acid bacteria strains isolated from the oral cavity of healthy people and lactobacilli strains isolated from various ecological niches are given in this article. Strains with high antagonistic activity against isolates of opportunistic microorganisms isolated in acute tonsillitis were selected. Their probiotic properties, such as sensitivity to antibiotics, adhesiveness and resistance to high salt content, have been studied.